P193 p53 and p16 expression profiles identify three prognostically subgroups in vulvar cancer: a TMA based study by the AGO-CaRE-translational study group. (1st November 2019) - Wölber, L; Prieske, K; Eulenburg, C; de Gregorio, N; Klapdor, R; Kalder, M; Braicu, I; Fuerst, S; Klar, M; Strauss, H-G; Mehlhorn, G; Meier, W; et al.
Abstract : Introduction/Background: Today, there are two accepted pathways for tumorigenesis of vulvar squamous cell carcinoma (VSCC): an HPV-dependent with p16 overexpression as a surrogate for HPV-associated transformation and an HPV-independent route linked to lichen sclerosus, characterized by p53 mutation. A possible correlation of HPV dependency with a favourable prognosis has been proposed. Methodology: The AGO CaRE-1 study is a retrospective survey of pts with primary VSCC FIGO stage ≥1B (UICC-TNM version 6) treated at 29 gynecologic cancer centers in Germany 1998–2008 (n=1, 618). For this CaRE-translational sub-study available FFPE tissue was collected centrally (n=648). A tissue micro array (TMA) was constructed; p16 and p53 expression was determined by immunohistochemistry (IHC). HPV status and subtype were analyzed by PCR. Results: p16 IHC was interpretable in 550 TMA spots and considered positive in 166/550 (30.2%). HPV DNA was detected in 78.4% of the p16+ tumors, with HPV 16 being the most common subtype (88.3%). p53 IHC was interpretable in 597 spots, 187/597 (31.3%) were considered positive. Pts with p53+ tumors were older at first diagnosis (71 vs. 66 yrs; p=0.001 for p53- tumors) and showed lymph-node involvement more often (43.3% vs. 31.1%; p=0.007). There was a relevant number of tumors with neither p16 nor p53 overexpression (221/535); while co-expression of p53 and p16 was rare (12/535). For survival analyses, three groups were defined: p53+ (n=163), p16+/p53- (n=151) and p16-/p53- (n=221). 2-y-disease-free (DFS) and overall survival (OS) rates were significantly different between the groups: DFS: p53+ 47.0%; p16-/p53- 53% and p16+/p53- 65.5% (p<0.001); OS: 70.4%, 72.6% and 82.7% (p=0.003), respectively. Adjustment for age and nodal status showed consistent p16 and p53 effects regarding DFS. Conclusion: p16 overexpression is associated with an improved prognosis in VSCC while p53 positivity is linked to an adverse outcome. Our data provide evidence of a clinically. Disclosure: The AGO CaRE translational study was supported by medac oncology without restrictions in the study protocol.